Prevalence of High Risk for Obstructive Sleep Apnoea and Its Risk Factors Among Adults Attending Government Primary Health Clinics in Kuantan - MA, Md Aris; AF, Amir Hamzah; F, Abdullah; ZA, Asha’ari (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Obstructive sleep apnoea (OSA) is a sleep-related breathing disorder with recurrent episodes of apnoea or hypopnoea occurring during sleep. It is associated with an increased risk of cardiovascular disease. However, there is no applicable study that assesses the risk for OSA at the primary care level. This study aims to assess the prevalence of risk for OSA and its associated risk factors among adults attending primary care clinics. MATERIALS AND METHOD: This cross-sectional study was conducted among 252 adults attending four Klinik Kesihatan in Kuantan, Pahang. A self-administered validated Malay version of the Berlin Questionnaire was used to screen for the High Risk of OSA. The statistical analyses were done using t-statistics and chi-squared test then proceeded with binary logistic regression. RESULTS: The mean age of respondents was 53.3. Most of the respondents were male (54%), Malay (87.7%), and married (79.4%). The prevalence of High Risk for OSA was 32.9%. Among these, 94% of them presented with snoring and 16.9% presented with excessive daytime sleepiness. The risk factors that were significantly associated with High Risk of OSA includes younger age (AOR=0.951 CI=0.923-0.980); higher Body Mass Index (BMI) classification with obese type 1 (AOR=2.604 CI=1.278-5.308), obese type 2 (AOR=3.882 CI=1.078-13.975) and obese type 3 (AOR=6.800 CI=1.164-39.717); higher neck circumference (AOR=1.109 CI=1.007-1.221); hypertension (AOR=2.297 CI=1.122-4.702); and hypercholesterolaemia (AOR=2.040 CI=1.050-3.965). CONCLUSIONS: Nearly one-third of the adults attending primary health clinics were at High Risk for OSA. Screening for OSA was recommended particularly among those of younger age, higher BMI classification, and with co-morbidities.